Relaciones humanas en mypes de Arequipa - Arias Gallegos, Walter Lizandro (2013)
The present research settles as aim, to determine the kind of human relations which prevail in small and medium enterprises (SMEs) at Paucarpata district from Arequipa City. In order to, we use the Human Relations Questionnaire with acceptable levels of validity and reliability (α = 0,648) and discriminate between four types of human relations: unsecure, collaborative, selfish and hostile. The results point that predominant human relations in SMEs are the hostile type, and make us to suppose that work conditions don’t benefit employees and could even have negative consequences in their job performance and welfare.